2014
DOI: 10.1105/tpc.114.125880
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Localization and Function of the Membrane Trafficking Regulator GNOM ARF-GEF at the Golgi Apparatus inArabidopsis 

Abstract: GNOM is one of the most characterized membrane trafficking regulators in plants, with crucial roles in development. GNOM encodes an ARF-guanine nucleotide exchange factor (ARF-GEF) that activates small GTPases of the ARF (ADP ribosylation factor) class to mediate vesicle budding at endomembranes. The crucial role of GNOM in recycling of PIN auxin transporters and other proteins to the plasma membrane was identified in studies using the ARF-GEF inhibitor brefeldin A (BFA). GNOM, the most prominent regulator of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 75 publications
(135 reference statements)
6
108
0
Order By: Relevance
“…Most of the plant PM proteins, including receptors, constitutively cycle between PM and endosomal compartments, a mechanism that modulates their abundance and activity (19). Therefore, to investigate whether PEPR1 also undergoes recycling, we applied the fungal inhibitor brefeldin A (BFA), which is also routinely used to block recycling in plants through inhibition of the BFA-sensitive ADPribosylation factor-guanine exchange factors (ARF-GEFs) (20). Following treatment with BFA (50 μM, 60 min), PEPR1-GFP fluorescence clearly accumulated in BFA bodies that were also costained with the endocytic tracer FM4-64 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the plant PM proteins, including receptors, constitutively cycle between PM and endosomal compartments, a mechanism that modulates their abundance and activity (19). Therefore, to investigate whether PEPR1 also undergoes recycling, we applied the fungal inhibitor brefeldin A (BFA), which is also routinely used to block recycling in plants through inhibition of the BFA-sensitive ADPribosylation factor-guanine exchange factors (ARF-GEFs) (20). Following treatment with BFA (50 μM, 60 min), PEPR1-GFP fluorescence clearly accumulated in BFA bodies that were also costained with the endocytic tracer FM4-64 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, it was shown recently that ENDOSIDIN8 interferes with the localization of PIN1 at the basal plasma membrane without affecting the polarity of apical proteins, and it was proposed that transport of PIN1 in the early secretory pathway may require GNOM/GNL1 function (Doyle et al, 2015). Notably, it has been shown that GNOM localizes mainly to the Golgi apparatus (Naramoto et al, 2014). Here, we found that interfering with the function of GNL1 causes an accumulation of newly synthesized PIN1 at internal structures with a morphology consistent with the ER.…”
Section: Discussionmentioning
confidence: 99%
“…BFA treatments inhibit GNOM, causing the accumulation of the internalized auxin effluxer PIN1 in aggregating GNOM-positive intracellular compartments (Geldner et al, 2003). However, superresolution/ electron microscopy studies showed its exclusive localization to Golgi cisternae, thereby challenging its function solely in protein recycling (Naramoto et al, 2014). In support, GNOM was recently implicated in the ER-toGolgi transport of PIN1 (Doyle et al, 2015).…”
Section: Tgn As An Ee: Two Directions But How Many Lanes?mentioning
confidence: 99%